The role of family socialization in determining the roleof girl in the Algerian family - ladjelat, fatimaahlam.; azouz, abdenaceu (Journal of Social Sciences and Humanities, 2020)
This research deals with "The role of family socialization in stereotyping girls’ role in the Algerian family." It comes as a scientific response, to know the change manifestations in the girl socialization over her role in modern family compared to traditional family, this; after the social, cultural and economic changes witnessed by the world and the Algerian society. That is considered as an adaptive response to what is happening in society; to meet new demands on the one hand, and on the other hand to keep up with what is happening in the contemporary world. This situation created a conflict and a problematic between the traditional values system and the modern value system in raising a girl - the modern value system imposed itself, and gets a kind of social acceptance. Therefore, the research aims to empower the Algerian family in raising the girl on her roles according to what is culturally and socially determined without violate the requirements of modern life as an active component in society. It has been revealed through this research that there is a set of processes that family socialization depends on in stereotyping the girl role, some of which are carried out in a conscious (intentional) way and others in an unconscious way, where the concept of the model and the female bond with themother, plays an important role in acquiring behaviours related to her role as a female, the most important of these processes are reincarnation, imitation, autism, and control. Differentiation in socialization takes place from the first years of a child's life, and this process is carried out in a collective manner, in which everyone participates. For the type of girl socialization in the traditional family, the girl represents the honour of the family, so she is surrounded by special care, as she is obliged to comply with strict values and standards, and she is prepared to take up household tasks. While in the modern family, and after the change that knew the Algerian society, socialization is no longer based on gender Differentiation, education and work have contributed to give her independence and a kind of emancipation, new values have emerged, and socialization is no longer based on her preparation for domestic life; Rather, it is for life as a whole